Sequência de ensino investigativa no ensino de soluções químicas - Hemann, Katiuscia Carla Viezzer (My University, 2024)
The teaching of Chemistry should enable high school students to have a comprehensive and integrated understanding of the chemical transformations that occur in the physical world. To achieve this, it is necessary to prioritize the teaching-learning process in a contextualized, problematizing, and dialogical manner, stimulating students' reasoning and helping them recognize the importance of Chemistry in the social context. Since Chemistry is essentially an experimental science, experimentation can be used as a way to motivate students to learn the content of this discipline, although it is not always easy to promote it due to the lack or poor condition of laboratories in the school environment. Experimental activities in Chemistry classes can be organized and proposed with different objectives, and although all may be valid, the choice of a specific type will mainly depend on the goals to be achieved. Investigative practical activities must have some significance for the student, avoiding "practice for practice's sake." Although this type of activity is not easy to plan, it provides remarkable development for students who play an active role in the teaching-learning process. This work aimed to develop and apply a didactic sequence consisting of three investigative practical activities for teaching Chemical Solutions in high school. The activities can be conducted in the classroom and involve the use of simple materials or substitutes in case there is no laboratory or equipment available. The didactic sequence aims to answer, through an active methodology such as the Investigative Teaching Sequence (ITS), grounded in experimental activities with different levels of openness, the research question: "Is determining the average solubility of potassium chloride at the temperatures of our region, which is rich in vineyards, important for farmers and consequently for the local economy? Therefore, what is the solubility of potassium chloride between 5 ºC and 15 ºC? How can these low temperatures affect the purpose of fertilization?" Finally, considerations on the success of the investigative approach reveal that the methodology helped promote students' curiosity and engagement, understanding of the concepts involved in solutions, use of chemical language, and comprehension of quantitative aspects. Furthermore, reinforcing activities that promote molecular visualization, such as computational simulations and graphical representations, can be an effective strategy to overcome the learning difficulties still observed in understanding the microscopic levels of molecules in this study and reported in the literature. [resumo fornecido pelo autor]
O ensino de Química deve possibilitar aos estudantes de Ensino Médio uma compreensão abrangente e integrada das transformações químicas que ocorrem no mundo físico. Para isso, é necessário priorizar o processo de ensino-aprendizagem de forma contextualizada, problematizadora e dialógica, estimulando o raciocínio dos estudantes e fazendo com que percebam a importância da Química no contexto social. Como a Química é uma ciência essencialmente experimental, a experimentação pode ser utilizada como forma de motivar os estudantes para o aprendizado dos conteúdos desta disciplina, embora nem sempre seja fácil promovê-la devido à inexistência ou precariedade de laboratórios no ambiente escolar. As atividades experimentais nas aulas de Química podem ser organizadas e propostas com diferentes objetivos e, embora todas possam ser válidas, a escolha de um tipo específico dependerá, principalmente, dos objetivos que se pretende alcançar. Atividades práticas investigativas devem ter algum significado para o estudante, evitando a realização da "prática pela prática". Apesar deste tipo de atividade não ser fácil de ser planejada, proporciona notável desenvolvimento dos estudantes que têm papel ativo no processo ensinoaprendizagem. Esse trabalho teve como objetivo elaborar e aplicar uma sequência didática constituída por três atividades práticas investigativas para o ensino de Soluções Químicas no Ensino Médio. As atividades podem ser realizadas em sala de aula e envolvem a utilização de matérias simples ou substituintes no caso de não haver laboratório ou equipamentos. A sequência didática tem o intuito de responder através de uma metodologia ativa como a Sequência de Ensino Investigativa (SEI), alicerçadas nas atividades experimentais com diferentes níveis de abertura, a questão de pesquisa: "A determinação da solubilidade média do cloreto de potássio nas temperaturas de nossa região que é rica em videiras é importante para os agricultores e, consequentemente, para a economia local. Sendo assim, qual a solubilidade do cloreto de potássio entre 5 ºC e 15ºC? Como estas baixas temperaturas podem afetar no propósito da adubação?" Por fim, as considerações sobre o sucesso da abordagem investigativa revelam que a metodologia ajudou a promover a curiosidade e o engajamento dos alunos, a compreensão dos conceitos envolvidos nas soluções, utilização da linguagem química e compreensão dos aspectos quantitativos. Ademais, reforçar as atividades que promovem a visualização molecular, como simulações computacionais e representações gráficas, pode ser uma estratégia eficaz para superar as dificuldades de aprendizagem ainda observadas na compreensão dos níveis microscópicos das moléculas neste estudo e reportadas no referencial bibliográfico. [resumo fornecido pelo autor]
Keywords: Química - Estudo e ensino; Aprendizagem; Química - Ensino médio; Chemistry - Study and teaching; Learning; Chemistry - High school